MEMBACA KONSTRUKSI JATI DIRI DAN PERUBAHAN PERSPEKTIF DALAM FILM ANIMASI SWAPPED - Rianti Nurul; Listia Zahara; Melly Maulyang; Rhafly Tandela; Richard Surbakti; Ita Khairani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the construction of identity and the transformation of perspectives in the Netflix animated film Swapped (2026), directed by Nathan Greno and produced by Skydance Animation. Using qualitative descriptive research methods with a narrative analysis approach, this study identifies how the body-swap mechanism is employed as a literary device to expose the fluidity of identity and the formation of new perspectives in two main characters, Ollie the Pookoo and Ivy the Javan. The analysis reveals three major findings: (1) the characters' identities are socially and culturally constructed through the collective memories and belief systems of their respective groups; (2) the physical body-swap experience serves as a catalyst that fundamentally disrupts previously held identity assumptions; and (3) the empathy generated through direct experiential interaction produces a qualitative shift in the characters' worldview. This study concludes that Swapped employs the body-swap narrative not merely as a comedic device, but as a vehicle for a profound social message: that prejudice and distrust rooted in group identity can only be dismantled by genuinely inhabiting another's lived experience. This film is highly relevant as educational media for cultivating empathy and social tolerance among young audiences.